Leadership Role Based on Islamic Values Productivity Work - Aep Syaeful Millah; Rosdita Indah Yuniawati (Indonesian Journal of Multidisciplinary Science, 2026)
This study examines the role of Islamic leadership values in enhancing employee work productivity through a systematic literature review. Contemporary organizations operating within an increasingly competitive global environment require leadership models that not only optimize managerial performance but also cultivate the ethical, moral, and spiritual dimensions of the workforce. Despite numerous empirical studies demonstrating the positive influence of Islamic leadership on organizational outcomes, a significant research gap persists: there remains limited conceptual and comprehensive literature that systematically integrates specific Islamic leadership values namely amanah (trustworthiness), siddiq (honesty), 'adl (justice), fathanah (wisdom and intelligence), and tabligh (communicativeness) as interconnected drivers of sustainable work productivity. This study therefore aims to analyze the theoretical mechanisms through which Islamic leadership values influence work productivity in modern organizational contexts. Employing a qualitative descriptive approach through library research, data were collected from scientific journals, books, theses, dissertations, and relevant documentary sources published between 2018 and 2026. The findings indicate that Islamic leadership values exert a significant positive influence on employee work productivity through four interconnected mechanisms: strengthening intrinsic motivation and spiritual work ethic, cultivating organizational discipline and accountability, building employee loyalty and commitment, and minimizing internal workplace conflict. Furthermore, Islamic leadership principles demonstrate strong conceptual alignment with participatory management, ethical leadership, and servant leadership models in modern organizations. This study contributes a holistic theoretical framework bridging Islamic values with organizational productivity determinants, providing practical implications for leaders in educational institutions, sharia-based enterprises, and public sector agencies.